The revolving door of life : a 44 Scotland Street novel - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- 44 Scotland Street series., 2016)
For seven-year-old Bertie Pollock, life in Edinburgh's most celebrated fictional street has just got immeasurably better. The enforced absence of his endlessly pushy mother Irene - currently consciousness-raising in a Bedouin harem (don't ask) - has manifold and immediate blessings: no psychotherapy, no Italian lessons and no yoga classes. Bliss. For Scotland Street's grown-ups, life throws up some new dilemmas. Matthew makes a discovery that could make him even richer but also leaves him worried. Pat makes one that could make her poorer and her father miserable - unless that uber-narcissist, Bruce, can help her out. And the Duke of Johannesburg, we discover, isn't exactly who he says he is. From what happens behind Edinburgh Airport's luggage carousel to Machiavellian manoeuvrings at the Association of Scottish Nudists, Alexander McCall Smith guides us through the brighter, lighter and frankly unexpected side of Edinburgh life. As ever with his 44 Scotland Street series, his readers will make their own discovery: that its blend of wit and wisdom mark it out as a comedic tour de force.